Claudins: from gatekeepers of epithelial integrity to potential targets in hepato-pancreato-biliary cancers - Jeon, Hyein; Sterpi, Michelle; Mo, Christiana; Bteich, Fernand (Frontiers in Oncology, 2024)
Claudins, a family of tetraspan transmembrane proteins, are critical to the integrity of tight junctions in epithelia and endothelia, influencing cellular processes such as development, differentiation, and apoptosis. Abnormal claudin expression is associated with various malignancies, particularly affecting tissue architecture and potentially facilitating tumor invasion and metastasis. In this comprehensive review, we explore the multifaceted functions of claudins: their expression, specific roles in cancer with a focus on hepato-pancreato-biliary malignancies and highlight their potential as therapeutic targets. We discuss current claudin-targeted therapies, including monoclonal antibodies, antibody-drug conjugates, bispecific T-cell engager and chimeric antigen receptor T-cell therapies. These approaches show promise in pre-clinical and clinical studies, particularly in hepato-pancreato-biliary cancers with large unmet needs. Despite these early signs of efficacy, challenges remain in effectively targeting these proteins due to their structural resemblance and overlapping functions.